Learning design of a programming and robotics MOOC for childhood teachers and educators - Mendes, António Quintas (2022)
In early childhood, the curricular integration of computational thinking, programming, and robotics topics is ever more pressing. Therefore, preparing teachers and educators to implement this integration in the curriculum is fundamental. In the project «Laboratory of Technologies and Learning of Programming and Robotics in basic and pre-school education in Portugal», the proposal of a MOOC was designed to meet this demand. This paper discusses aspects of the architecture of MOOCs, and their typologies, in the context of the challenges that the researchers encountered in the design process of the present MOOC. To do so, the Interaction Equivalency Theorem was considered, which equates the fundamental types of interaction to be considered in course design (learner-instructor; learner-content; learner-learner). Considering that learning design is both a process and a product the design of the MOOC is analysed in terms of its socio-technical context and systemic tensions present in work-based learning. Through a qualitative analysis of an individual interview and of a focus group, the paper describes formal and informal interactions and attempts to define a common vision, consensus, and divergences and contradictions that are part of the learning design process. Finally, the MOOC is presented, and its pedagogical design is substantiated.